The Effects of a Severe Fire on the Steel Frame of an Office Building - Dexter, Robert J.; Lu, Le-Wu (Engineering Journal, 2001)
This paper discusses the effects a severe fire had on a steel high-rise frame. The damage to this frame was no worse than in other fire-damaged steel-framed buildings such as the Alexis Nihon hotel in Montreal and the Broadgate in London. The yield strengths of the columns were not significantly decreased. There were locked-in residual moments and forces. However pushover analyses of simple frames with and without residual moments show that the stability and lateral load carrying capacity of the frames were unaffected by residual moments, as would be expected from the principles of plastic analysis. The steel frame and floor system of this building could have been reinstated relatively quickly, as has been done in comparable fire-damaged steel-framed high-rises.